Role of Organochlorine Pesticides in Children with Idiopathic Seizures. (3rd December 2013) - Arora, Shilpa Khanna; Batra, Prerna; Sharma, Tusha; Banerjee, Basu Dev; Gupta, Sushan
Abstract : Background . Organochlorine pesticides (OCP) are persistent organic pollutants that have been implicated in causing several deleterious effects in humans. These are known neurotoxins in high doses, but the role of environmentally acquired OCPs in the body to induce seizures in children has not been investigated yet. Objectives . To assess the serum levels of OCPs in children aged 2–12 with idiopathic seizure and to find out any association between the two are our objectives. Methods . It was a cross-sectional pilot study. Twenty developmentally normal children aged 2–12, presenting with idiopathic generalized seizures, were recruited. Twenty age-matched controls without any history of seizures were also taken. Their serum levels of α, β, and γ hexachlorocyclohexane (HCH); and aldrin; dieldrin; p, p-dichlorodiphenyltrichloroethane (DDT), o, p-DDT, and p, p dichlorodiphenyldichloroethylene (DDE); and α and β endosulfan were analysed using gas chromatography (GC). Mann-Whitney U test was used to compare OCP levels between the groups. Spearman correlation was used to find the correlation between individual pesticide levels with age and seizure duration. Results . Levels of β, γ, and total HCH were significantly higher among cases as compared to the control group (P ≤ 0.05 ). Conclusion . There exists a possible association between idiopathic seizures and high serum levels of OCPs, especially HCH.